1997
DOI: 10.1007/s002469900194
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Atrial Insertion Sites of Left-Sided Accessory Pathways in Children: Efficacy and Safety of Transseptal Versus Transaortic Approach

Abstract: Left-sided accessory pathways are a common substrate for supraventricular tachycardias in children. A transseptal approach to catheter ablation has been primarily advocated in this population because of concerns regarding vascular injury, aortic, and mitral valvular damage using the transaortic approach via retrograde femoral arterial cannulation. However, the transaortic approach is simpler and may be less time consuming. We, therefore, compared the efficacy and safety of the transseptal vs the transaortic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…With respect to children two studies stand out: Vora et al 12 obtained a 100% success rate in the ablation of left APs in their atrial insertions using the RA access in 36 patients and the TS access in thirteen. They reported a shorter FT for the RAA technique (p = 0.05) 12 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With respect to children two studies stand out: Vora et al 12 obtained a 100% success rate in the ablation of left APs in their atrial insertions using the RA access in 36 patients and the TS access in thirteen. They reported a shorter FT for the RAA technique (p = 0.05) 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall the studies suggest that the differences found between the techniques may be related to the learning curve and to the experience of the operator, rather than to the specifi c technique used 12,13 . When we began this study the group was more experienced with procedures via RA, and only one operator had received training in TS puncture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations